Land Abandonment in Indonesia: Perspective of National Land Law and Islamic Law - Adinata, Hendrix; Ichsan, Muchammad (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2023)
The increasing number of people causes the need for land to increase. On the other hand, there is still a lot of land neglect by individuals and legal entities, giving rise to social, economic, and people's welfare disparities and reducing environmental quality. This study aims to determine and analyze land abandonment from the perspective of national land law and Islamic law. The writing method uses juridical-normative legal research examining library materials or secondary data. The research results show that land abandonment from the perspective of national land law is currently regulated in the Regulation of the Government of the Republic of Indonesia Number 20 of 2021 concerning Controlling Abandoned Areas and Land. Abandoned freehold land becomes the object of control over abandoned land with the provision that it is not used, exploited, or maintained for 20 years. Meanwhile, land with building use rights, use rights, management rights, and business use rights becomes the object of controlling abandoned land if it is not used, utilized, or maintained for two years from the issuance of the rights. Meanwhile, from the perspective of Islamic law, land abandonment can be seen from the opinions of the Hambali, Syafi'i, and Maliki Fuqaha. The Hambali School stipulates three years for cultivating land. If the land cannot be developed within that time, the rights to the land will be lost, and the State will take the land to be distributed to other people. Meanwhile, the Syafi'i and Maliki schools do not determine a specific period but solely based on why the ground is not cultivated.